Changing Anxiety into Excitement Is Better Than Calmness in Public Speaking - Kusuma, Perdana; Lukman, Lukman; Hamid, Andi Nasrawaty (Budapest International Research and Critics University, 2021)
Individuals often feel anxious when they are about to perform or anticipate an important task to be done, for example prior speaking publicly, or meeting with a supervisor. Anxiety drains working memory, decreases self-confidence and harms performance. Majority of people believe trying to calm down is the best way to cope with anxiety, and individuals believe that this way is the best way to slow down before doing an important task (pre-performance). Early studies found that students faced with situations that cause anxiety (pre-performance anxiety), were more likely to answer that the most appropriate way to deal with anxiety is by calming down. They believe that this way is better than accepting the experience, avoiding situations that cause anxiety, or reappraise anxiety as excitement.The main study of the current research is to test whether stating to myself